Leukemia and Its Impact on the Quality of Life of a Child: A Case Study - Rahmawati, Mila; Nanik; Probowati, Yusti (ANIMA Indonesian Psychological Journal, 2011)
The purpose of this study was to allow a leukemia patient to describe their health related quality of life (HRQoL) in their own words, in order psychologists could understand the impact that leukemia has on children. Four semistructured interview questions guide the interviews. Each question related to a domain identified in previous researches as having an effect on HRQoL. Areas explored were (a) physical well-being and symptoms, (b) psychological well-being, (c) social well-being, and (d) functional well-being. Five themes were identified: (a) fatigue, (b) the effect on activities, (c) medi- cation and treatment effects, (d) relationship changes, and (e) hair loss. In addition, based on content analysis, the result showed that there is an interactive effect between the diseases and the level of QoL. The results reveal that the social, physical and emotional health and well-being of children with acute lymphocytic leukemia (ALL) is significantly poorer than their community-based peers. Tujuan penelitian ini adalah menuntun penyandang leukemia limfostik akut mendeskripsikan kualitas hidupnya yang terkait kesehatan dengan kata-katanya sendiri, agar para psikolog dapat memahami dampak leukimia pada anak. Wawancara dipandu empat pertanyaan interviu semi- terstruktur. Tiap pertanyaan terkait ranah yang teridentifikasi penelitian terdahulu memiliki dampak pada kualitas hidup terkait kesehatan. Wilayah yang dieksplorasi adalah (a) kesejahteraan dan gejala fisik, (b) kesejahteraan psikologis, (c) kesejahteraan sosial, (d) kesejahteraan fungsional. Ditengarai lima tema: (a) kelelahan, (b) akibat pada aktivitas, (c) akibat pengobatan dan perawatan, (d) perubahan hubungan, (e) kehilangan rambut. Selain itu, berdasarkan analisis isi, hasil menunjukkan bahwa terdapat akibat interaktif antara penyakit dan tingkat kualitas hidup. Hasil menunjukkan bahwa kesehatan sosial, fisik dan emosi, serta kesejahteraan anak penyandang leukimia limfositik akut lebih rendah secara bermakna daripada teman sebayanya di masyarakat